SEXUAL BEHAVIOUR AND DETERMINANTS AMONG SECONDARY-SCHOOL ADOLESCENTS IN BENUE STATE, NIGERIA: A MIXED-METHODS CROSS-SECTIONAL STUDY - Ali, Ojumu Charles (African Journal of Social and Behavioural Sciences, 2025)
This mixed-methods cross-sectional study assessed sexual behavioural patterns and their determinants among secondary school students in Benue State, Nigeria. A multi-stage sampling technique was used to select 400 students (JSS 1-SS3) from six co-educational schools, who completed a structured questionnaire; 12 in-depth interviews and four focus group discussions provided contextual depth. The prevalence of sexual activity was 41.3% (165/400), with 52.7% of sexually active students initiating sex between ages 13 and 15. Risky patterns were prevalent: 58.8% did not use a condom at last sex, 66.7% had two or more partners, and contexts included peer pressure (37.6%) and transactional sex (27.3%). Guided by the Theory of Planned Behaviour, key determinants included favourable attitudes towards sex (e.g., as a sign of maturity, 46.3%), strong subjective norms (43.0% believed most friends were sexually active), and low perceived behavioural control (only 33.0% were confident refusing sexual advances). Qualitative data contextualized these findings, revealing peer networks as primary sources of information and pressure. The study concludes that risky sexual behaviour is multifaceted, driven by attitudinal, normative, and control factors. A multi-tiered programme is recommended: scale up comprehensive, age-appropriate sexuality education; support peer-led prevention campaigns; and broaden access to confidential, youth-friendly sexual health services. Limitations include self-report bias and the non-causal nature of the cross-sectional design.